2008
DOI: 10.1002/app.27851
|View full text |Cite
|
Sign up to set email alerts
|

A novel and green method for polycondensation reaction of 4‐substituted phenylurazoles with different diisocyanates under solvent‐free conditions

Abstract: In this investigation, a new method for stepgrowth polymerization reactions of 4-phenylurazole (PHU) and 4-(4-methoxyphenyl)urazole (MPU) with various diisocyanates were developed under solvent-free conditions. The reaction of these monomers with hexamethylene diisocyanate (HMDI), isophorone diisocyanate (IPDI), and tolulyene-2,4-diisocyanate (TDI) were performed in the presence or absence of dibutyltin dilaurate (DBTDL) as a catalyst. The results of polymerization revealed that DBTDL did not have considerable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…To compare the microwave-assisted method with conventional heating, we also performed the polymerization reactions under conventional heating (method II) [35]. In this method, polymerization was carried out by heating the monomers via one-step high temperature which took very long time (12 h versus 5 min ) compared to method I.…”
Section: Using: Rapid Solid-state Microwave-assisted Technique 319mentioning
confidence: 99%
See 1 more Smart Citation
“…To compare the microwave-assisted method with conventional heating, we also performed the polymerization reactions under conventional heating (method II) [35]. In this method, polymerization was carried out by heating the monomers via one-step high temperature which took very long time (12 h versus 5 min ) compared to method I.…”
Section: Using: Rapid Solid-state Microwave-assisted Technique 319mentioning
confidence: 99%
“…This could pertain to the aromatic, rigid structure of diisocyanate for PU6AI in comparison with the aliphatic and flexible structure of others PUs. The thermal behaviors of these polymers (method I) were also compared with PUs synthesized by a conventional method (method II) [35] and the results indicated that PUs prepared by solid-state condition under microwave had higher thermal properties according to the higher inherent viscosities USING: RAPID SOLID-STATE MICROWAVE-ASSISTED TECHNIQUE 323 (table 5). The polymers, PU4AI, PU5AI and PU6AI showed 10% weight loss at 283, 279 and 308 2 C, respectively.…”
Section: Thermal Propertiesmentioning
confidence: 99%